ANALYSIS OF THE ENERGY MARKET OPERATOR ACTIVITY IN EIGHT EUROPEAN COUNTRIES - France Krizanic; Zan Jan Oplotnik (Innovative Issues and Approaches in Social Sciences, 2015)
The article aims to analyze the connection between economic development, energy consumption, and prices of electricity and gas on one side and of the operation of the Energy Market Operator on the other. For this purpose we use a sample of eight EU countries with well-functioning energy markets but quite diverse characteristics. The results show that Market Operators in more developed countries in the sample have above average activity (according to revenue), and their primary goal is to achieve external economies. A higher level of Market Operator activity (greater revenue) is influenced by the decrease of transaction costs in energy markets and improves the prospect for greater use of energy. An active Market Operator is characteristically associated with international openness in the energy market as well as with the development of gas use in the given country. We find that a better equipped (greater assets used by the Market Operator) and more active (according to revenues) Market Operator is related with relatively higher levels of electricity and natural gas prices.